2021
DOI: 10.1007/s12559-021-09978-8
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Deep Learning and Belief Rule Base Intelligent System to Predict Survival of COVID-19 Patient under Uncertainty

Abstract: The novel Coronavirus-induced disease COVID-19 is the biggest threat to human health at the present time, and due to the transmission ability of this virus via its conveyor, it is spreading rapidly in almost every corner of the globe. The unification of medical and IT experts is required to bring this outbreak under control. In this research, an integration of both data and knowledge-driven approaches in a single framework is proposed to assess the survival probability of a COVID-19 patient. Several neural net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The results of Khozeimeh et al's 58 study also showed that one of the most important features related to the mortality of patients with COVID-19 was heart disease. The results of studies of Ahmed et al 54 and Cisterna-García et al 56 similar to the results of our study, identified the features of lung disease, blood pressure, and acute respiratory distress syndrome as effective factors in the development of a predictive survival system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of Khozeimeh et al's 58 study also showed that one of the most important features related to the mortality of patients with COVID-19 was heart disease. The results of studies of Ahmed et al 54 and Cisterna-García et al 56 similar to the results of our study, identified the features of lung disease, blood pressure, and acute respiratory distress syndrome as effective factors in the development of a predictive survival system.…”
Section: Discussionsupporting
confidence: 92%
“…data set. 53 Various studies [54][55][56][57][58][59][60][61] were conducted in predicting the survival and mortality of COVID-19 patients using ML techniques. Krajah's et al 59 study showed intubation was the most important features for the survival prediction.…”
Section: Nb Classifier Can Classify All the Cases Of Death Correctly ...mentioning
confidence: 99%
“…None of these features were identified as the ten most important features in predicting survival in our model. In the study of Ahmed et al the characteristics of blood pressure, chronic obstructive pulmonary disease, blood sugar, asthma, chronic kidney disease, obesity, acute respiratory distress syndrome, and pulse oximetry were used as effective factors in developing a predicting survival system [37]. In line with these results, in our study, the important role of blood pressure, kidney disease, and lung problems has been proven in terms of survival prediction.…”
Section: Discussionsupporting
confidence: 75%
“…Other scholars established a carbon dioxide absorption desorption process optimization system based on the product life cycle theory by using the life cycle cost method [4]. Some scholars applied the principles of supply chain environmental management and resource allocation to build a multi-stage linear solution based on single objective integer programming, solved the problem of mismatch between carbon emission peak and emission reduction benefit indicators, and achieved comprehensive energy conservation and cost reduction effect [5][6]. Therefore, based on integrated intelligence, this paper studies and discusses the optimization of the peak path of industrial carbon emissions in Shanghai.…”
Section: Introductionmentioning
confidence: 99%